Effect of filler particles on surface roughness of experimental composite series - Hanadi Yousif Marghalani (University of São Paulo, 2010)
OBJECTIVE: The purpose of this study was to evaluate the effect of different filler sizes and shapes on the surface roughness of experimental resin-composite series. MATERIAL AND METHODS: Thirty-three disc-shaped specimens of the series (Spherical-RZD 102, 105, 106, 107, 114 and Irregular-RZD 103, 108, 109, 110, 111, 112) were prepared in a split Teflon mold and irradiated with an halogen light-curing unit (450 mW/cm² for 40 s) at both top and bottom surfaces. The specimens were stored for 3 months in distilled water. The surface roughness values in form of surface finish-vertical parameter (Ra), maximum roughness depth (Rmax) and horizontal roughness parameter (Sm) were recorded using a contact profilometer. The data were analyzed by one-way ANOVA and the means were compared by Scheffé post-hoc test (a=0.05). RESULTS: The lowest surface roughness (Ra) was observed in S-100 (0.079±0.013), while the roughest surface was noted in I-450/700/1000 (0.125±0.011) and I-450/1000 (0.124±0.004). The spherical-shape series showed the smoothest surface finish compared to the irregular-shape ones with higher significant difference (p>0.05). The vertical surface roughness parameter (Ra) values increased as the filler size increased yielding a linear relation (r²=0.82). On the contrary, the horizontal parameter (Sm) was not significantly affected by the filler size (r²=0.24) as well as the filler shape. CONCLUSIONS: Filler particle's size and shape have a great effect on the surface roughness parameters of these composite series.